2015
DOI: 10.1128/aac.00496-15
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Comparison of Posaconazole Levels in Patients Taking the Delayed-Release Tablet versus the Oral Suspension

Abstract: While posaconazole prophylaxis decreases the risk of invasive fungal infection compared to fluconazole, low bioavailability of the oral-suspension formulation limits its efficacy. A new delayed-release tablet formulation demonstrated an improved pharmacokinetic profile in healthy volunteers. However, serum levels for the two formulations have not been compared in clinical practice. This study compared achievement of therapeutic posaconazole levels in patients taking the delayed-release tablet to those taking t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
35
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 16 publications
9
35
1
Order By: Relevance
“…The tablet and intravenous formulations were approved on the basis of safety and pharmacokinetic data, with corresponding phase III data for the tablet formulation recently being published (9). To date, several small, single-center studies have reviewed the initial implementation of PCZ tablets, focusing mainly on pharmacokinetic endpoints (5,6,(10)(11)(12). In agreement with our early experience, those reports also have shown that PCZ tablets yield higher serum concentrations than the suspension formulation and appear to be safe (5).…”
supporting
confidence: 66%
“…The tablet and intravenous formulations were approved on the basis of safety and pharmacokinetic data, with corresponding phase III data for the tablet formulation recently being published (9). To date, several small, single-center studies have reviewed the initial implementation of PCZ tablets, focusing mainly on pharmacokinetic endpoints (5,6,(10)(11)(12). In agreement with our early experience, those reports also have shown that PCZ tablets yield higher serum concentrations than the suspension formulation and appear to be safe (5).…”
supporting
confidence: 66%
“…We did not find a significant relationship between age and posaconazole CL/F, which could be owing to the fact that our youngest patient was 6 months old, whereas rapid pharmacokinetic maturation tends to occur in the neonatal to early infant age group [12]. The gastro-resistant tablet formulation has been widely reported to have improved bioavailability over the suspension [21][22][23][24]. In addition, suspension bioavailability has previously been reported to be saturable in adults [25][26][27][28], although we are not aware of this relationship having previously been modelled using the population approach.…”
Section: Discussionmentioning
confidence: 51%
“…3B) and 0.868 mg · h/liter (95% CI, 0.743 to 0.993 mg · h/liter) for predicting satisfactory PPCs at late steady state. This is the largest study to date that explores pre-steady-state (11). In contrast to what was done in our study, a significant proportion of patients in the study by Durani et al received PCZ delayed-release tablets, which may not only explain the higher PPCs obtained in that study but also indicate that accumulation of PCZ may be an important factor in patients with very high PPCs at pre-steady state.…”
contrasting
confidence: 55%
“…(1)(2)(3)(4)(5)(6) and is currently approved for antifungal prophylaxis in patients with prolonged neutropenia and in patients with acute graft-versus-host diseases (GVHDs) after hematopoietic stem cell transplantation (HSCT) (7)(8)(9)(10). PCZ is available as an oral suspension and lately also as a delayed-release tablet formulation and an intravenous formulation (11)(12)(13). Due to the potentially lower costs and easier intake than for the delayed-release tablet, the oral suspension remains in use for antifungal prophylaxis (14).…”
mentioning
confidence: 99%